Effect of eight weeks' selected resistance training on serum levels of estradiol, sex hormone-binding globulin (SHBG) and body composition in obese and overweight premenopausal women - mandana gholami; reihaneh tathirimoghaddam (Shahid Beheshti University, 2019)
Purpose: Among the most important sex hormones that changes in their levels are related to different diseases pathogenesis can mentioned to sex hormone binding globulin (SHBG) and estradiol. Therefore, the aim of present study was to investigate the effect of eight weeks' selected resistance training on serum levels of estradiol, sex hormone-binding globulin (SHBG) and body composition in overweight premenopausal women.Methods: Twenty premenopausal women assigned in two experiment (mean age 44.3±2.11 years) and control (mean age 42.3±5.37 years) groups. Experiment group performed resistance training for eight weeks, three sessions in week by using Thera band. resistance exercise consist of 16 movements for upper body, trunk and lower body. Each movement performed with 10 repetitions, 3 set and two-minute interval rest between sets and one minute's rest between exercises. 48 hours after the last exercise session, blood samples collected and desired variables (SHBG and estradiol) were measured by Elisa method. Data analyzed by analyze covariance test.Results: Increase the SHBG and decrease of body fat percent were significant in training group. But, changes in serum levels of estradiol wasn't significant statistically.Conclusion: Different type of exercise training play important role in modulation of sex hormones levels. According to present study results, probably resistance training with Thera band have positive effects on modulate of sex hormones levels in women with overweight.